2017
DOI: 10.1136/archdischild-2017-313009
|View full text |Cite
|
Sign up to set email alerts
|

Burden of child and adolescent obesity on health services in England

Abstract: There is a mismatch between population burden and available data on service use for obesity in CYP in England, particularly among deprived young people. There is a need for consistent evidence-based commissioning of services across the childhood obesity pathway based on population burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…(n = 410 000) of 2 to 14 year olds with obesity in England were eligible for secondary care referral; 17 however, our findings suggest that in a cohort of children born at the beginning of the new millennium, increased admissions in early childhood and adolescence are not directly attributable to childhood obesity. Our findings are, however, not a cause for complacency, given the rising prevalence of obesity in subsequent generations of children born in the United Kingdom after this cohort and the lack of follow-up into adult life possible currently.…”
Section: M00-m99 83 68contrasting
confidence: 59%
See 3 more Smart Citations
“…(n = 410 000) of 2 to 14 year olds with obesity in England were eligible for secondary care referral; 17 however, our findings suggest that in a cohort of children born at the beginning of the new millennium, increased admissions in early childhood and adolescence are not directly attributable to childhood obesity. Our findings are, however, not a cause for complacency, given the rising prevalence of obesity in subsequent generations of children born in the United Kingdom after this cohort and the lack of follow-up into adult life possible currently.…”
Section: M00-m99 83 68contrasting
confidence: 59%
“…Obesity prevention strategies remain key to reducing the prevalence and impact of childhood obesity, and more research is needed to support evidence-based commissioning of health care services for the management of obesity in CYP. 17…”
Section: M00-m99 83 68mentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive research has shown an association between the increase in SSB consumption and childhood overweight and obesity [ 31 , 32 , 33 ]. According to the latest report on Chinese Residents’ Chronic Diseases and Nutrition in 2020, the prevalence of overweight/obesity in children and adolescents aged 6~17 years was 19% in 2016, which increased by 5.0% from 2012 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%